The economic impact of streaming beyond GDP. Issue 5 (12th March 2022) - Edquist, Harald; Goodridge, Peter; Haskel, Jonathan
ABSTRACT: This article finds that the shift from buying music as a physical product towards subscribing to music services implies an unmeasured decrease of 85% in the price paid per song. Traditionally, price indexes have focused on tangible prices on CDs. These price indexes have partly become obsolete as more of the consumption of music is streamed. However, the price indexes for streamed music still do not capture the price paid per song. We estimate that the shift from buying CDs to streaming music online generates a price decrease of 85% per song. This implies that in 2019 the global quality-adjusted value from streamed music was $76 billion compared to current revenues of $11 billion. Thus, the shift from consuming music in physical form towards subscribing to music services creates an enormous consumer surplus that is not recorded in GDP.